Review of microbiota gut brain axis and innate immunity in inflammatory and infective diseases - Yuan, Chongshan; He, Yuhong; Xie, Kunyu; Feng, Lianjun; Gao, Shouyang; Cai, Lifu (Frontiers in Cellular and Infection Microbiology, 2023)
The microbiota gut brain (MGB) axis has been shown to play a significant role in the regulation of inflammatory and infective diseases. Exploring the structure and communication mode of MGB axis is crucial for understanding its role in diseases, and studying the signaling pathways and regulatory methods of MGB axis regulation in diseases is also of profound significance for future clinical research. This article reviews the composition, communication mechanism of MGB axis and its role in inflammatory and infective diseases, including Parkinson’s disease (PD), Alzheimer’s disease (AD), multiple sclerosis (MS), autism spectrum disorder (ASD), depression, psoriasis, irritable bowel syndrome (IBS), and inflammatory bowel diseases (IBD). In addition, our investigation delved into the regulatory functions of the inflammasome, IFN-I, NF-κB, and PARK7/DJ-1 innate immune signaling pathway in the context of inflammatory and infective diseases. Ultimately, we discussed the efficacy of various interventions, including fecal microbiota transplantation (FMT), antibiotics, probiotics, prebiotics, synbiotics, and postbiotics, in the management of inflammatory and infective diseases. Understanding the role and mechanism of the MGB axis might make positive effects in the treatment of inflammatory and infective diseases.